Zoo Simulator to Increase Children Learning Phase - Rendy Rendy; Marcel Bonar Kristanda; Seng Hansun (Institute of Advanced Engineering and Science, 2017)
The growth of kids' brain could be optimized by recognizing something. Learning to recognize animals is one of the methods to stimulate the children's brain growth to imagine. Nevertheless, kids tend to spend all their time by playing and could not focus to recognize the animals due to the way of learning which is usually not interactive and not interesting. Therefore, a game application was designed and developed to be used as a way to help children in recognizing the animals. This program was developed as a mobile game application with the animation and attractive display to increase the kids' interest to learn the animals. Beside that, Fisher-Yates shuffle algorithm has been successfully implemented on the game to randomize the images which can be found on puzzles, randomize the answers in image guessing puzzles, randomize animals to choose which can be sold, randomize the foods which will be given to the pets, and randomize the initial position to create patterns on rescue rare animal puzzles. After the implementation and testing on the game application, it proves that it could increase the kids’ interest in learning new animals to 4.18 in ARCS interest measuring index compare with textbook method which only 2.74.